Genomic and Phenotypic Characterisation of Campylobacter jejuni Isolates From a Waterborne Outbreak - Davies, Emma; Ebbesen, Marit; Johansson, Cecilia; Kaden, René; Rautelin, Hilpi (Frontiers in Cellular and Infection Microbiology, 2020)
Campylobacter infections are the leading cause of bacterial gastroenteritis. In Europe, over 246,000 cases are confirmed annually. Infections are often transmitted via contaminated food, such as poultry products, but water may be the source of infection as well. The aim of this study was to characterize a selection of Campylobacter jejuni human isolates, together with a water isolate, from a waterborne outbreak in Norway in 2019, including human isolates from early, mid- and late epidemic. The isolates were characterized with whole-genome sequencing, analysing the expression of putative virulence genes and demonstrating the pathogenic potential in an in vitro adhesion model using HT-29 cells. All isolates belonged to the multilocus sequence type 1701 and ST45 clonal complex. In the genomic analysis, the water isolate clustered somewhat separately from the human isolates. There was some variation between the human isolates, but the water isolate displayed clearly the greatest pathogenic potential, demonstrated by the highest levels of virulence gene expression, adhesion to epithelial cells and IL-8 induction. These results suggest that the water isolate of the study has potential to cause human infections, and that some bacterial changes due to host or environmental adaptation, may occur during a waterborne Campylobacter epidemic. This is, to the best of our knowledge, the first study on C. jejuni isolates from a waterborne outbreak, including both human isolates and a water isolate, characterized with genomic and phenotypic approaches.